Realisasi Manajemen Kelas Berdasarkan Psikologi Dalam Pendidikan Anak Sekolah Dasar - Nadya Wahyu Pramita; Arba'iyah Yusuf; M. Ilhamsyah Fauzan Akbar; Naili Aulia Rahmani (Peneliti.net, 2023)
Classroom management is a way for educators to create or maintain a comfortable classroom environment for the students. Linking psychology with classroom management as a foundation will potentially result in the world of education being favored and liked by students, especially for elementary school-age children. This is because elementary school children usually have strong and capable physical characteristics at the age of 6 to 12 years, when they enter the world of education, moreover at that age they are not too dependent on their parents. And it is common knowledge that education is something that is important and must be obtained by everyone, because this education affects everyone's intelligence, mindset, and future. Good classroom management will make elementary school children to college get and feel a comfortable educational environment. Especially if this is based on psychology, which relates to and relates to the behavior and characteristics of students so that it helps educators more easily create/maintain a comfortable educational environment.